FUNDAMENTAL PROBLEMS OF INVESTMENT FUNDS IN UKRAINE FROM THE POINT OF VIEW OF COMPLEMENTARY PENSION PROVISION OF CITIZENS - MORHACHOV, ILLIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The relevance and urgent need for the formation of complementary pension provision for the population in Ukraine has been determined. The complementary pension provision of the citizens of the country is considered as not at all implying the complete destruction of the existing solidarity pension system, but only the formation of additional mechanisms that make the pension provision of citizens generally successful even in the existing conditions. Such a mechanism can be a set of investment funds (joint investment institutions) in the country, which will add to the existing solidarity pension system elements of capital accumulation through the activation of investment processes. The purpose of the work was to determine the fundamental problems and prospects of Ukrainian investment funds (joint investment institutions) from the point of view of complementary pension provision for citizens in Ukraine. The purpose of the work was to determine the fundamental problems and prospects of Ukrainian investment funds (joint investment institutions) from the point of view of complementary pension provision for citizens in Ukraine. The article defines that the prerequisite for effective complementary provision is the optimal balance structure, which is similar to such better analogues as the Berkshire Hathaway and the Vanguard S & P 500 ETF. It is specified that the formation of a balance sheet structure in accordance with the best foreign analogues contradicts the current regulatory framework in the country, which is a fundamental problem in the formation of complementary pension provision on the basis of joint investment institutions. It is determined that the majority of investment funds existing in Ukraine in the form of joint investment institutions (ISI) under the current legislation are not able to provide a complementary pension for citizens of the country at a sufficient level of efficiency due to the impossibility of forming an optimal asset structure. The fundamental problem of ISI in the country is the legislative restrictions on the formation of the optimal structure of their balance. The optimal balance sheet structure of the investment fund, in particular assets (dominated by shares of the world’s leading companies) and liabilities (dominated by equity and raised funds by issuing bonds) is the basis for the effectiveness of complementary pension provision.